Proceso de ASC - MUSEO DE LOS ESFUERZOS INUTILES ETAPA 2 (2022)
It is an installation in which thirteen useless objects are exhibited in conjunction with thirteen musical pieces. The curatorial text accompanying each useless object is a literary minifiction in the form of ironic instructions for use. The installation seeks to immerse the visitor in a sensory and cognitive experience that engages them in reflections and imaginings about the utility and futility of many human practices, desires, and projects. The idea is that through objectual, auditory, and textual materializations, an exploratory spirit is activated around the meaning of many vital efforts and even around the need to lucidly and aesthetically embrace their meaninglessness.